2008
DOI: 10.1007/s10555-008-9124-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase epsilon and Neu-induced mammary tumorigenesis

Abstract: Aberrant regulation of the phosphorylation of proteins on tyrosine residues is a well-established cause of cancer. Protein tyrosine phosphatases (PTPs) share in the crucial function of maintaining appropriate levels of phosphorylation of cellular proteins, making them potentially key players in regulating the transformation process. The receptor-type tyrosine phosphatase Epsilon (RPTPepsilon) participates in supporting the transformed phenotype of mammary tumor cells induced in vivo by the Neu tyrosine kinase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 105 publications
2
15
0
Order By: Relevance
“…Cells from mammary epithelial tumors initiated by HER2 in PTP⑀ knock-out mice confirmed these findings by appearing less transformed morphologically and with reduced cell proliferation (25). Together, these findings suggest that PTP⑀ is necessary for the fully transformed phenotype of HER2-induced mouse mammary tumor cells (4).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Cells from mammary epithelial tumors initiated by HER2 in PTP⑀ knock-out mice confirmed these findings by appearing less transformed morphologically and with reduced cell proliferation (25). Together, these findings suggest that PTP⑀ is necessary for the fully transformed phenotype of HER2-induced mouse mammary tumor cells (4).…”
mentioning
confidence: 53%
“…From our screening, we found PTP⑀ of special interest since this PTP had previously been related with the transformation of mouse mammary tumors (4). However, the association of PTP⑀ with human breast cancer has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, PTP" has been viewed as a promising candidate because it is overexpressed in murine mammary tumors and experiments have demonstrated that PTP" plays a positive role in cell growth and survival in MCF-7 cells and other breast cancer cell lines (Elson, 1999(Elson, , 2017Elson & Leder, 1995). Additional data have shown that PTP" (and the closely related PTP) are positive regulators of HER2mediated and Src-mediated signaling in breast cancer cells (Parsons & Parsons, 2004;Berman-Golan et al, 2008). Src is a major player in breast cancer, and dephosphorylation of its C-terminal regulatory phosphotyrosine (pTyr530) by PTP" triggers a cascade of events that lead to the activation of Src, which favors a transformed phenotype (Espada & Martín-Pé rez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of alterations of specific PTP functions have been reported in cancer cells, including gene deletion, allele loss, reduced expression by promoter methylation, or inactivation by point mutation or oxidation, all leading to loss-of function [1,2]. Upregulation of expression, or gain-of-function mutations have also been found for members of the PTP family, which have been shown or presumed to promote oncogenesis [1-4]. …”
Section: Introductionmentioning
confidence: 99%